Effects of xanthan gum based biopolymer treatment on hydraulic conductivity of silty sand - Jodin Makinda; Elsa Eka Putri; Cemmellia Anisha Mosungin; Lillian Gungat (Universitas Andalas, 2025)
Soil permeability, influenced by void spaces within the soil, is crucial properties in suitability of silty sand in various applications. Silty sand, comprising sand and silt particles, is more permeable than finer-grained silts and clays, making its use as a sealing medium challenging due to its natural porosity. This study investigates xanthan gum, a sustainable biopolymer, as a soil stabilizer to address these challenges. The focus is on the hydraulic conductivity of silty sand treated with varying percentages of xanthan gum and subjected to different curing times. Soil samples from the Likas River, known for its silty sand deposits, underwent laboratory testing, including soil classification and constant head permeability tests according to BS Standard. The soil is then treated using xanthan gum of 0.1, 0.5 and 1.0%, and under 1, 3 and 7 curing days. Results revealed that xanthan gum addition significantly reduced soil permeability, with 1.0% and 7-day curing as the optimum treatment, reducing the hydraulic conductivity from 6.442 m/s to 0.150 m/s. The reduction is attributed to enhanced soil particle interactions, increased contact areas, and stronger particle bonds upon xanthan gum addition. The results show the potential of xanthan gum applications in geotechnical engineering such as construction of clay liner, groundwater contamination control, dam and embankment and soil subgrade. The study lays the foundation for future research on the broader application of biopolymers in soil stabilization, contributing to the advancement of sustainable geotechnical engineering solutions.